Electrode biasing maintains the edge shear layer at high density in the J-TEXT tokamak. (1st July 2022) - Ke, R.; Diamond, P.H.; Long, T.; Xu, M.; Chen, Z.P.; Gao, L.; Yang, Q.H.; Wang, Y.H.; Zhang, X.Y.; Nie, L.; Wu, T.; Gao, J.M.; et al.
Abstract: Collapse of the edge flow shear as the line-averaged density approaches the Greenwald density limit has been observed as a precursor to the enhanced edge particle flux characteristic of proximity to the density limit regime. Here, we report the use of a biased electrode to sustain the edge shear layer in high density discharges, in which the shear layer would otherwise collapse. A stable increase in line-averaged density is observed along with a strong increase in edge density. These experiments were carried out on the J-TEXT tokamak. The Reynolds stress at the edge is enhanced, and the zonal flow sustained, while density perturbation levels, the flux of turbulence internal energy (i.e., turbulence spreading), and particle and heat flux all decrease significantly. Electron adiabaticity increases, and bias voltage modulation experiments show that an increase in the edge shear leads the increase in adiabaticity. These results suggest that external edge E × B flow shear drive may be of interest for sustaining edge plasma states at high density, and support the hypothesis that collapse of the edge shear layer triggers the onset of the strong transport and turbulence characteristic of the density limit regime.